Single Coronary Artery: A Case Report - W Mustapha, Wan Irfan; Mohd Yusof, Mubarak (2021)
Coronary artery congenital anomalies can be classied based on the origin, course, and termination of the arteries. The majority of patients with these anomalies have no symptoms. They can, however, be accompanied by shortness of breath, palpitation, and even myocardial infarction symptoms.